On vibration of hanging pendulum in hammer crusher - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1984)
In- this article the vibration of hanging pendulum in hammer crusher is investigated in case when the ratio p2 /l2 is not very small in comparison with 1. It turned out that the suitable parameters in this case are 33% larger than that in the case p2 /l2 <<1 [1]. Because there is the friction the pendulum vibrates not around straight line OA but around A’ with an angle x0 determined by (4.3), (4.4 ).